THE EFFECT OF GLOBAL MACROECONOMIC ON INDONESIAN TEA TRADE IN INTERNATIONAL MARKET - Sibuea, Faiz Ahmad; Sibuea, Mhd. Buhari; Sibuea, Siti Rahmah (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2025)
The aim of the research is to analyze of competitiveness Indonesian tea trade in international market, the factors that influence the value of Indonesian tea exports in the and to analyze the long-term influence of export tariffs and Non-Tariff Measures (NTM) consisting of sanitary and phytosanitary on the value of Indonesian tea exports in the main destination countries. This research using secondary data in the form of panel data with RCA model, the Gravity Model and long-term influence analysis with Fully Modified Ordinary Least Square (FMOLS). The results of research show the competitiveness of Indonesian tea has been great where the RCA value higher than 1. In addition, the variables that have a significant influence on the value of Indonesian tea exports are export tea prices, imported tea prices, export tariffs and the NTM dummy, while the exchange rate and economic distance variables do not have a significant effect on the value of tea exports. In the long term, Indonesia's tea trade policy, which consists of export tariffs and dummy Non Tariff Measures (NTM), has a long-term influence on the value of tea exports.